Current management strategies for multidrug-resistant Gram-negative urinary tract infections, a focus on aminoglycosides monotherapy - Iris Zohar; Yasmin Maor; Neta Shirin; Dafna Yahav (CMI Communications)
Background: Urinary tract infections (UTI) are common, with increasing rates of multidrug resistant pathogens in some countries. Recent trials suggest efficacy of new beta-lactam beta-lactamase inhibitors compared to carbapenems, piperacillin-tazobactam, or quinolones for UTI; however, these newer drugs, as well as the comparators, should probably be reserved for severe and/or non-urinary infections. Aminoglycosides have broad Gram-negative spectra, achieve high concentrations in the urinary system, and are associated with low collateral damage to microbiota compared to beta-lactams and quinolones. Objective: To summarize the evidence supporting the use of aminoglycosides as both empirical and definitive therapy for UTI, mainly in areas with high rates of multidrug-resistant Gram-negative organisms. Source: Published medical literature (Medline via Pubmed). Content and implications: Recent data show high susceptibility rates of Enterobacterales to amikacin, second only to susceptibility to plazomicin and carbapenems. Accumulating evidence from older randomized controlled trials and recent observational studies demonstrates no difference in mortality or clinical response between aminoglycosides and comparators, while newer data suggest that with proper dosing and monitoring, aminoglycosides are safe. Nephrotoxicity rates, once a main concern with aminoglycosides, have been demonstrated in recent studies to be similar to those of other antibiotics when aminoglycosides are administered once daily. Current international guidelines also recommend aminoglycosides as a treatment option for complicated UTI and pyelonephritis. Additional studies are needed to provide updated data on nephrotoxicity and ototoxicity rates using once daily dosing with/without therapeutic drug monitoring.